1978
DOI: 10.1007/bf00344692
|View full text |Cite
|
Sign up to set email alerts
|

Grasshopper food habits within a shrub-steppe community

Abstract: Results from a dietary analysis of eight grasshopper species inhabiting a shrub-steppe community in southeastern Washington showed that 15 vascular plant species served as food items. Several plant species occurred at higher frequencies in the diet samples than in the plant community. Big sagebrush (Artemisia tridentata) was the most frequently selected plant species, followed by turpentine cymopterus (Cymopterus terebinthinus), green rabbitbrush (Chrysothammus viscidiflorus), and Carey's balsamroot (Balsamorh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 6 publications
2
20
0
Order By: Relevance
“…During the 5-year study, grasshopper density increased and then declined. High grasshopper densities are typical for Palouse prairie (12,13). At this site, mammalian herbivores, ranging in size from Bison bison (636 kg) to Microtus pennsylvanicus (3.5 ϫ 10 Ϫ2 kg), were abundant (Ϸ2.5 g͞m 2 ), densities similar to those reported by early explorers of the Great Plains (5-9 g͞m 2 ) (14, 15).…”
Section: Methodsmentioning
confidence: 52%
“…During the 5-year study, grasshopper density increased and then declined. High grasshopper densities are typical for Palouse prairie (12,13). At this site, mammalian herbivores, ranging in size from Bison bison (636 kg) to Microtus pennsylvanicus (3.5 ϫ 10 Ϫ2 kg), were abundant (Ϸ2.5 g͞m 2 ), densities similar to those reported by early explorers of the Great Plains (5-9 g͞m 2 ) (14, 15).…”
Section: Methodsmentioning
confidence: 52%
“…3.12) (Allred 1941;Graham and others 1995;Sheldon and Rogers 1978). Sheldon and Rogers (1978), studying the food habits of eight species of grasshoppers, found that seven of the eight consumed some big sagebrush, but Melanoplus cinereus was the champion big sagebrush eater (61 percent of its diet). Sheldon and Roger (1978) Sheldon and Rogers (1978, p. 89-90) further observed:…”
Section: Crickets Grasshoppers and Katydidsmentioning
confidence: 96%
“…The information on the type of food utilized by the ground grasshoppers could not be gathered in this study. Shelton & Rogers (1978) and Pfadt & Lavigne (1982) have reported that some grasshoppers feed on algae, fungi, detritus matter, humus and moss found on ground. Braker (1989) has reported that most of the grasshoppers, particularly the members of the superfamily Acridoidea lay eggs in soil.…”
Section: Resultsmentioning
confidence: 99%